Sustainable And Traditional Product Innovation Without Scale And Experience, But Only For KIBS! (2018)
This study analyzes the ideal strategic trajectory for sustainable and traditional product innovation. Using a sample of 74 Costa Rican high-performance businesses for 2016, we employ fuzzy set analysis (qualitative comparative analysis) to evaluate how the development of sustainable and traditional product innovation strategies is conditioned by the business' learning capabilities and entrepreneurial orientation in knowledge-intensive (KIBS) and non-knowledge-intensive businesses. The results indicate two ideal strategic configurations of product innovation. The first strategic configuration to reach maximum product innovation requires the presence of KIBS firms that have both an entrepreneurial and learning orientation, while the second configuration is specific to non-KIBS firms with greater firm size and age along with entrepreneurial and learning orientation. KIBS firms are found to leverage the knowledge-based and customer orientations that characterize their business model in order to compensate for the shortage of important organizational characteristics-which we link to liabilities or smallness and newness-required to achieve optimal sustainable and traditional product innovation.